Steeping Tin Leaves (Ficus carica) Improves Sperm Quality of Male Mice (Mus musculus) Exposed to Lead Acetate - Emi Kusumawardani; Budi Santoso; Widjiati; Hari Basuki Notobroto; Heru Santoso Wahito Nugroho (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: Lead can induce lipid oxidation in cell membrans, thus forming free radicals. The process of imbalance of free radicals and antioxidants will disrupt the normal function of cells, causing cell death and decreased sperm quality. Purpose: The purpose of this research is to explain the mechanism of steeping tin leaves (Ficus carica) increase sperm quality in male mice (Mus musculus) exposed to lead acetate. Methods: This type of research was true experimental design with posttest only control group design with the number of replications of 10 male mice, the experimental unit will be distributed proportionally to 5 groups. Steeping tin leaves will be given with a dose of Pb + Tin Leaf 1.664 mg (P1) and Pb + Tin Leaf 3.328 mg (P2), while for lead acetate dose 0.5 mg and quercetin dose 0.7 mg. The analyzed variables included spermatozoa motility, spermatozoa morphology, and spermatozoa concentration. Data analysis was conducted including the Shapiro-Wilks normality test, and the homogeneity test used the Levene test. If the data were not homogeneous, the group average test would use the Brown-Forsythe test, then continued with a different test for each group using the Post Hoc Games-Howell test. If the Levene test data were homogeneous, the group average test would use Oneway Anova. Findings: The results showed that giving of steeping tin leaves with a dose of Pb + Tin leaves 3.328 mg (P2) is able to increase spermatozoa motility and spermatozoa morphology. Conclusion: The steeping tin leaves increase sperm quality